Post-Dural Puncture Headaches Treated by Bilateral Greater Occipital Nerve Block with a Ropivacaine-Onabotulinum Toxin Mixture - Régis Fuzier; Geneviève Salvignol (International Journal of Pain, 2025)
The greater occipital nerve block (GONB) and Onabotulinum toxin A have been proposed for the treatment of different headache types. However, the combination of these two techniques in post-dural puncture headache (PDPH) management has not been previously described. We report, for the first time, the case of a 32-year-old woman treated successfully for PDPH using bilateral GONB with a ropivacaine-Onabotulinum toxin A mixture. Adding Onabotulinum toxin A to ropivacaine significantly extended the duration of analgesia compared to ropivacaine alone (2.5 months vs. 3 days).